Arthur and the Crunch Cereal Contest. - Brown, Marc Tolon (Brown, Marc Tolon. Marc Brown Arthur chapter book, 1998)
When Arthur hears his sister singing a catchy tune, he wonders if he could call that jingle his own and enter it in the Crunch Cereal Contest.